Simulation and analysis of voltage and electric field distribution along high voltage insulator - Yee, Choon Sean (2022)
High voltage insulators play a major rule in energy transmission systems. The main role of these insulators is to ensure and maintain high level of line-tower insulation. However, the voltage distribution of insulator string is uneven which may easily lead to corona, insulators’ surface deterioration and even flashover. Although there is various research for this topic, but there still have some limitations regarding on the performance of insulator in terms of voltage and electric field distributions. In this project, high voltage insulator strings with will be designed and simulated by using simulation software such as SOLIDWORKS and EMS software and their data (electric field and voltage distributions) will be collected and analysed. The modelling of the insulator will be designed by considering the effect of conductor and transmission tower as well as different material type of high voltage insulator such as porcelain, glass and silicon rubber. In addition, the improvement on the performance of the insulator also will be taken into consideration in this project. The research described in this dissertation is directly applicable to the Voltage and Electric Field distributions along the high voltage insulators design and development.